Surface modification of smooth poly (L-lactic acid) films for gelatin immobilization - Li, Hai (2013)
Poly(l-lactic acid) (PLLA) is widely used in drug delivery and medical implants. Surface modification of PLLA with functional groups to immobilize gelatin or other extracellular matrix proteins is commonly used to improve its cellular affinity. In this work, we use the oxygen plasma to treat PLLA film followed by modification with organosilanes with different functional groups, such as amine, epoxy, and aldehyde groups. Gelatin is then immobilized on the modified PLLA film, which is confirmed by water contact angle measurement, atomic force microscopy (AFM), and laser scanning confocal microscopy (LSCM). Among the used organosilanes, aminosilane is the best one for modification of PLLA used for immobilization of gelatin with the highest efficiency. Moreover, the cellular affinity of gelatin-immobilized PLLA is studied through the evaluation of cell proliferation and focal adhesion using the human umbilical vein endothelial cells (HUVECs). Our experimental results show that the gelatin immobilized on aminosilane- and aldehyde-silane-modified PLLA improves the cellular affinity of HUVECs, whereas that immobilized on epoxy-silane-modified PLLA does not show significant improvement on the cell proliferation.